Analisis kinerja profitabilitas Bank Syariah Indonesia (BSI): melalui Rasio Return on Assets (ROA) periode 2020–2024 - Aspasya, Marsha Aura; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study analyzes the profitability performance of Bank Syariah Indonesia (BSI) using the Return on Assets (ROA) ratio for the 2020–2024 period by integrating empirical findings from various studies on the determinants of Islamic banking profitability in Indonesia and other relevant countries. The main issue addressed is the fluctuation of Islamic banks’ ROA driven by internal factors (capitalization, financing, asset quality, operational efficiency) and external factors (inflation, policy interest rates, and macroeconomic conditions), while BSI as a merged bank operates with a much larger asset scale and higher operational complexity. The review shows that Islamic banks’ ROA is highly sensitive to operational efficiency ratios (BOPO/OER) and financing quality (NPF), whereas the impact of capital adequacy (CAR) and financing (FDR/total financing) depends on the effectiveness of fund intermediation and risk management. Cross-study evidence also indicates that economic growth and macroeconomic stability tend to strengthen ROA, while inflationary pressures and increases in policy interest rates can erode low-cost funding and profit margins. Overall, BSI needs to balance its financing expansion strategy with strict control of operating costs and financing risk so that ROA remains within a healthy category in line with regulatory standards.